Scientific Advances in Controlling Nosema ceranae (Microsporidia) Infections in Honey Bees (Apis mellifera) - Burnham, Andre J. (Frontiers in Veterinary Science, 2019)
Honey bees (Apis mellifera) are agriculturally important pollinators that have been recently at risk to severe colony losses. A variety of parasites and pathogens have been linked to colony decline, including the microsporidian parasite Nosema ceranae. While fumagillin has been used to control nosemosis in managed honey bee colonies for decades, research shows that this antibiotic poses a toxic threat and that its efficacy against N. ceranae is uncertain. There is certainly a demand for a new veterinary medication to treat honey bee colonies infected with N. ceranae. In this review, recent scientific advances in controlling N. ceranae infections in honey bees are summarized.